Effects of pH, Temperature and Agitation on the Decolourisation of Dyes by Laccase-Containing Enzyme Preparation from Pleurotus sajor-caju - Bettin,Fernanda (2019)
(1) Background: In this study, the effects of different pH values ​​(2.4, 3.2, 4.4 and 5.0), temperatures (30, 35, 40, 45 and 50°C) and agitation (100 rpm) on the enzymatic decolourisation of twenty-two dyes belonging to the chromophore groups anthraquinone, azo and triphenylmethane were assessed. (2) Methods: In all conditions, it was used a crude enzyme broth containing 30 U mL-1 laccases produced by Pleurotus sajor-caju PS-2001 in submerged process. (3) Results: Regarding the effects of pH values, the best results were obtained at pH 3.2 and 30°C, in which bleaching was observed for all dyes evaluated. In assays conducted at different temperatures, highest levels of decolourisation were observed at 35°C and pH 3.2 for nineteen of the dyes assessed. Thirteen dyes presented colour reduction exceeding 50% after the enzymatic treatment, including all acid and all disperse dyes evaluated. The reciprocal agitation of 100 rpm promoted negative effect on decolourisation. (4) Conclusion: From the results achieved, one can conclude that the laccase-containing preparation of P. sajor-caju PS-2001 has potential for the decolourisation of some dyes widely used in different industrial sectors, especially in the textile industry, and therefore could be used in future strategies for the biotreatment of coloured wastes.